2017
DOI: 10.3846/16484142.2016.1252946
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of traffic sign vandalism that obstructs critical messages to drivers

Abstract: Abstract.A critical deficiency in any one or a combination of three transportation system characteristics: the driver, roadway, or vehicle can contribute to an elevated crash risk for the motoring public. Traffic signs often convey critical information to drivers. However, traffic signs are only effective when clearly visible and legible. Traffic sign vandalism that is exclusively the results of humans causes both sign legibility and visibility to deteriorate. Transportation agencies spend a significant amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Khalilikhah and Heaslip utilized Random Forest (RF) to predict traffic sign vandalism as the function of several predictor variables such as mount height, size, background color, exposure, land cover, and road type [21]. Chi-square test results showed that there was a significant association between all the sign attributes and vandalism.…”
Section: Related Workmentioning
confidence: 99%
“…Khalilikhah and Heaslip utilized Random Forest (RF) to predict traffic sign vandalism as the function of several predictor variables such as mount height, size, background color, exposure, land cover, and road type [21]. Chi-square test results showed that there was a significant association between all the sign attributes and vandalism.…”
Section: Related Workmentioning
confidence: 99%